Analisis Pengelolaan dan Perlakuan Akuntansi Aset Tetap di Desa Jatiwangi Kecamatan Cikarang Barat Kabupaten Bekasi - Mutia, Nafa Farha; Ulupui, I Gusti Ketut Agung; Perdana, Petrolis Nusa (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This research aims to determine the implementation of village asset management and the application of fixed asset accounting in Jatiwangi Village, West Cikarang District, Bekasi Regency. Data analysis in this research was guided by Permendagri No. 01 of 2016 and PP No. 71 of 2010 Statement No. 07. This research is a type of qualitative research with a descriptive approach, used primary data by conducting direct interviews with six informants, and secondary data in the form of documents owned by Jatiwangi Village related to village asset management and fixed asset accounting. The results of this research show that Jatiwangi Village has managed village assets quite well, there are six appropriate stages, namely planning, utilization, security, maintenance, assessment, and guidance and supervision, and four stages are not appropriate, namely procurement, use, administration and reporting, while the transfer and deletion stages have never been carried out. The results of research on the application of fixed asset accounting are not fully in accordance with the aspects contained in PSAP No. 07, recognition of fixed assets is not appropriate, initial assessment is appropriate, subsequent measurements have not been carried out, and disclosures have not been made.